Diaphragm and preparation method and application thereof

By adopting a polymer layer design with low coating amount and high coverage in the lithium-ion battery separator, the problem of insufficient interface wrinkles and adhesiveness after full filling of the existing separator is solved, and the reduction of membrane impedance and improvement of battery long cycle performance is achieved.

CN119921054APending Publication Date: 2025-05-02ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510163477.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have poor interfacial folding problems after full charge and insufficient adhesive force, resulting in low long cycle performance. When adding glue coating to improve adhesion, it is easy to cause hole blockage problems, increase the diaphragm impedance, and affect the dynamic performance of the battery cell.

Method used

The separator design with a low coating amount and a high polymer layer coverage is adopted, including a porous base film, a heat-resistant layer and a polymer layer. The polymer layer consists of a first adhesive, a second adhesive and a dispersant, with a coating amount of 0.3 g/m2-0.7 g/m2 and a coverage ratio of 25%-60%, to improve the adhesion of the separator and improve the interfacial fold problem.

Benefits of technology

It improves the adhesion and mechanical properties of the diaphragm, reduces the impedance of the diaphragm, improves the long circulation performance of the battery, and improves the conduction capacity of lithium ions, ensuring the high-temperature performance and chemical stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005272062150000191
    Figure BDA0005272062150000191
Patent Text Reader

Abstract

The invention provides a diaphragm as well as a preparation method and application thereof. The diaphragm comprises a porous base membrane, a heat-resistant layer provided on at least one surface of the porous base film; the heat-resistant layer is arranged on the surface of the porous base membrane, the polymer layer is arranged on the surface, far away from the heat-resistant layer, of the porous base membrane and / or the surface, far away from the porous base membrane, of the heat-resistant layer, the polymer layer comprises a first binder, a second binder and a dispersing agent, and when the coating amount of the polymer layer is 0.3 g / m < 2 >-0.7 g / m < 2 >, the coverage rate of the polymer layer is 25%-60%. According to the diaphragm as well as the preparation method and the application thereof, the diaphragm has low coating amount and relatively high polymer layer coverage rate, the binding power of the diaphragm is improved, the problem of interface wrinkles is solved, the impedance of the diaphragm is reduced, and the long cycle performance of a battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a diaphragm and a preparation method and application thereof. Background Art

[0002] In lithium-ion batteries, the diaphragm is set between the positive and negative pole pieces to physically isolate the positive and negative poles and prevent the occurrence of internal short circuits. At the same time, it also has the function of allowing lithium ions to pass through. With the requirements of lithium-ion batteries for energy density and safety performance, the diaphragm material is also required to be further thinned and improve heat resistance while having adhesion. The wet-process diaphragms on the market are basically a layer of ceramic layer coated on a polymer base film, followed by a layer of glue coating. The glue coating is mainly to solve the problem of interface wrinkles after full charge, but usually encounters the problem of insufficient adhesion, resulting in poor improvement of full charge interface wrinkles and insufficient long cycle performance. However, if a glue coating layer is added to improve the adhesion, it is found that the problem of interface wrinkles will not be improved due to the increase in the amount of glue in the glue coating layer. On the contrary, there will be an increase in the amount of glue coating, which is prone to pore blocking, resulting in an increase in the overall impedance of the diaphragm and affecting the dynamic performance of the battery cell. Summary of the invention

[0003] The present invention proposes a diaphragm and a preparation method and application thereof. Through the diaphragm with low coating amount and high polymer layer coverage and the preparation method and application thereof proposed in the present invention, the adhesion of the diaphragm can be improved, the interface wrinkle problem can be improved, the diaphragm impedance can be reduced, and the long cycle performance of the battery can be improved.

[0004] In order to solve the above technical problems, the present invention provides a diaphragm, comprising at least:

[0005] Porous base membrane;

[0006] a heat-resistant layer disposed on at least one surface of the porous base membrane; and

[0007] The polymer layer is disposed on the surface of the porous base film away from the heat-resistant layer and / or on the surface of the heat-resistant layer away from the porous base film, the polymer layer comprises a first binder, a second binder and a dispersant, and the coating amount of the polymer layer is 0.3 g / m 2 -0.7g / m 2 When the polymer layer is coated with water, the coverage rate is 25%-60%.

[0008] In one embodiment of the present invention, the ratio of the mass of the dispersant in the polymer layer per square meter to the material density of the first binder is 0.002-0.005:1, and the material density of the first binder is 0.6 g / cm 3 -1.2g / cm 3 .

[0009] In one embodiment of the present invention, the first binder includes at least one of polymethyl methacrylate or acrylate; the second binder includes at least one of acrylate, acrylonitrile or acrylic polymer, and the molecular weight of the second binder is greater than 600,000; the dispersant includes at least one of water-based styrene maleic anhydride, acrylic acid and its salts.

[0010] In one embodiment of the present invention, in the polymer layer, the mass ratio of the first binder to the dispersant is 75-400:1, and the mass ratio of the first binder to the second binder is 8-15:1.

[0011] In one embodiment of the present invention, the median particle size of the first binder is 5 μm-10 μm, and the median particle size of the second binder is less than 1 μm.

[0012] In one embodiment of the present invention, the thickness of the heat-resistant layer is 0.5 μm-2 μm, and the bulk density of the heat-resistant layer is 1.2 g / cm 3 ~2.0g / cm 3 .

[0013] In one embodiment of the present invention, the heat-resistant layer includes ceramic particles, and the ceramic particles include at least one of aluminum oxide, hydrated aluminum oxide, aluminum hydroxide, silicon dioxide, titanium dioxide, barium sulfate, barium titanate, magnesium hydroxide or magnesium oxide, and the structure of the ceramic particles is flaky, and the specific surface area / median particle size of the ceramic particles is in the range of 40-80.

[0014] In one embodiment of the present invention, the heat-resistant layer includes a third binder, and the ratio of the median particle size of the third binder to the median particle size of the ceramic particles is 0.01-0.1:1.

[0015] The present invention also provides a method for preparing the above-mentioned diaphragm, comprising:

[0016] Dispersing the first binder, the second binder and the dispersant in the first solvent according to a mass ratio to obtain a polymer slurry;

[0017] After mixing the third binder and the second solvent, adding ceramic particles and mixing evenly to obtain a heat-resistant slurry;

[0018] coating the heat-resistant slurry on at least one surface of a porous base film and drying; and

[0019] The polymer slurry is coated on a surface of the porous base membrane away from the heat-resistant layer and / or a surface of the heat-resistant layer away from the porous base membrane and dried.

[0020] The present invention also provides a lithium ion battery, comprising the above-mentioned diaphragm.

[0021] In summary, the present invention proposes a diaphragm and its preparation method and application, which can improve the uniformity of the formed polymer layer and obtain a uniformly coated polymer layer. It is possible to improve the mechanical properties of the diaphragm while taking into account flexibility, improve the ion transmission performance of the diaphragm, reduce the contact area with the electrolyte, and improve the chemical stability of the diaphragm. The obtained heat-resistant layer has a smooth and dense microscopic surface, and the actual contact area between the heat-resistant layer and the polymer layer is increased, thereby increasing the effective bonding area, improving the adhesion between the heat-resistant layer and the polymer layer, so that the overall adhesion of the diaphragm is improved, and the problem of cell interface wrinkles is improved, thereby improving the cycle performance of the battery. It is possible to improve the high temperature resistance of the diaphragm, improve the thermal shrinkage of the porous base film at high temperature, and ensure the smooth conduction of lithium ions. Through a diaphragm with a low coating amount and a high polymer layer coverage, the adhesion of the diaphragm is improved, the problem of interface wrinkles is improved, the diaphragm impedance is reduced, and the long cycle performance of the battery is improved. DETAILED DESCRIPTION

[0022] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0023] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0024] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] The present invention provides a diaphragm, comprising a porous base film, a heat-resistant layer and a polymer layer, wherein the heat-resistant layer is arranged on at least one surface of the porous base film, the polymer layer is arranged on a surface of the porous base film away from the heat-resistant layer and / or on a surface of the heat-resistant layer away from the porous base film, and the polymer layer comprises a first binder, a second binder and a dispersant, wherein the coating amount of the polymer layer is 0.3 g / m 2 -0.7g / m 2, the coverage of the polymer layer is 25%-60%, the coating amount refers to the mass of the coating material on the coated substrate per unit area, and the coverage refers to the proportion of the area that can be covered by the coating material per unit area. By using a polymer layer with a low coating amount and a high coverage rate, the adhesion of the diaphragm is improved, the interface wrinkle problem is improved, and the long cycle performance of the battery is improved. In the present application, at least the purpose of adjusting the coating amount and coverage of the polymer layer can be achieved by increasing the equipment slurry flow, reducing the slurry solid content, adjusting the rotor speed, etc.

[0026] In one embodiment of the present invention, the porous base film includes, for example, one or more of a polyethylene (PE) film, a polypropylene (PP) film, a non-woven fabric, a polyethylene terephthalate (PET) film, a polyimide (PI) film, or a polypropylene-polyethylene-polypropylene composite film. The thickness of the porous base film is, for example, 3 μm-20 μm, and the porosity of the porous base film is, for example, 20%-70%, where the porosity refers to the percentage of the pore volume in the bulk material to the total volume of the material in a natural state.

[0027] In one embodiment of the present invention, the polymer layer includes a first binder, a second binder and a dispersant, wherein the dispersant includes at least one of water-based styrene maleic anhydride, acrylic acid and its salts, and the first binder includes at least one of polymethyl methacrylate (PMMA) or acrylate. The material density of the first binder is 0.6 g / cm 3 -1.2g / cm 3 The ratio of the mass of the dispersant in the polymer layer per square meter to the material density of the first binder is 0.002-0.005:1. In the present application, the material density is an inherent property of the material, which is the mass per unit volume of the substance. By controlling the ratio of the mass of the dispersant to the material density of the first binder, the diaphragm has a low coating amount and a high polymer layer coverage.

[0028] In one embodiment of the present invention, the second binder includes, for example, at least one of polyacrylate polymers, polyacrylonitrile or acrylic polymers, and the molecular weight of the second binder is, for example, greater than 600,000. In the polymer layer, the mass ratio of the first binder to the dispersant is, for example, 75-400:1, and the mass ratio of the first binder to the second binder is, for example, 8-15:1. By controlling the ratio of the first binder, the second binder and the dispersant to improve the processing performance, the uniformity of the slurry dispersion can be improved, thereby improving the uniformity of the formed polymer layer and obtaining a uniformly coated polymer layer.

[0029] In one embodiment of the present invention, the median particle size (Dv 50 ) is, for example, 5 μm-10 μm, and the median particle size of the second binder is, for example, less than 1 μm. By controlling the median particle size of the first binder and the second binder, the mechanical properties of the diaphragm can be improved while taking into account the flexibility, the ion transmission performance of the diaphragm can be improved, the contact area with the electrolyte can be reduced, and the chemical stability of the diaphragm can be improved. Among them, the median particle size Dv 50 It refers to the diameter of the particle at 50% of the volume when the particles are arranged in order from small to large diameter.

[0030] In one embodiment of the present invention, the heat-resistant layer includes a third binder and ceramic particles, wherein the ceramic particles include at least one of aluminum oxide, hydrated aluminum oxide, aluminum hydroxide, silicon dioxide, titanium dioxide, barium sulfate, barium titanate, magnesium hydroxide or magnesium oxide, etc. The structure of the ceramic particles is, for example, flaky, the ratio of the specific surface area / median particle size of the ceramic particles is in the range of 40-80, and the ratio of the median particle size of the third binder to the ceramic particles is, for example, 0.01-0.1:1. The specific surface area is the total area per unit mass of material. By controlling the ratio of the specific surface area / median particle size of the ceramic particles and the ratio of the median particle size of the third binder and the ceramic particles, the surface roughness of the heat-resistant layer is, for example, 3Sz / μm-5Sz / μm. On the other hand, the average surface roughness of the heat-resistant layer is, for example, Ra<1, wherein the surface roughness Sz / μm is the height of the sum of the maximum profile peak height and the maximum profile valley depth within a sampling length such as 1μm, which reflects the sum of the maximum profile peak height and valley depth of the surface, and is usually used to evaluate the overall height change of the surface; the average surface roughness Ra is the arithmetic mean deviation of the surface profile within the sampling length, reflecting the average deviation of the surface height, that is, the average value of the surface height fluctuation. By controlling the surface roughness of the heat-resistant layer, the microscopic surface of the heat-resistant layer is smooth and dense, the actual contact area between the heat-resistant layer and the polymer layer is increased, thereby increasing the effective bonding area, improving the bonding force between the heat-resistant layer and the polymer layer, improving the overall bonding ability of the diaphragm, improving the problem of cell interface wrinkles, and thus improving the cycle performance of the battery.

[0031] In one embodiment of the present invention, the third binder includes at least one of polyacrylonitrile and copolymers thereof, polyacrylic acid and copolymers thereof, polyethylene, polyacrylate and copolymers thereof, styrene-butadiene copolymer, styrene-acrylate copolymer and fluorine-based polymer materials. The mass ratio of the third binder to the ceramic particles in the heat-resistant layer is, for example, 1:(15-20), the thickness of the heat-resistant layer is, for example, 0.5 μm-2 μm, and the bulk density of the heat-resistant layer is 1.2 g / cm 3 ~2.0g / cm 3, where the mass per unit volume of the heat-resistant layer is defined as the bulk density, which is calculated as follows: the density of the heat-resistant layer divided by the thickness of the heat-resistant layer, in g / cm 3 The heat-resistant layer density refers to the weight per unit area of ​​the heat-resistant layer. The specific calculation method is: the weight of the heat-resistant layer divided by the area of ​​the heat-resistant layer. The unit is g / cm 2 By controlling the thickness and stacking density of the heat-resistant layer, the high-temperature resistance of the separator is improved, the thermal shrinkage of the porous base membrane at high temperatures is improved, and the smooth conduction of lithium ions is ensured.

[0032] In one embodiment of the present invention, a method for preparing a diaphragm is also provided, which specifically includes: dispersing a first binder, a second binder and a dispersant in a first solvent in a mass ratio to obtain a polymer slurry; mixing a third binder and a second solvent, adding ceramic particles, mixing evenly, to obtain a heat-resistant slurry; coating the heat-resistant slurry on at least one surface of a porous base membrane and drying; coating the polymer slurry on the surface of the porous base membrane away from the heat-resistant layer and / or the surface of the heat-resistant layer away from the porous base membrane and drying.

[0033] In one embodiment of the present invention, the first solvent is water, for example, and in the polymer slurry, the total content of the first binder, the second binder and the dispersant is, for example, 5wt%-15wt%. The second solvent is water, for example, and the third binder and the second solvent are first mixed evenly, and then ceramic particles are added to improve the uniformity of the dispersion of the ceramic particles. In the heat-resistant slurry, the total content of the third binder and the ceramic particles is, for example, 30wt%-45wt%. By controlling the content of the solute in the polymer slurry and the heat-resistant slurry, the bulk density of the heat-resistant layer formed and the coating amount of the polymer layer can be controlled, thereby controlling the preparation process of the diaphragm.

[0034] In one embodiment of the present invention, the heat-resistant slurry is coated by micro-gravure coating or wire rod coating, and then dried to obtain a heat-resistant layer. Then, the polymer slurry is coated on the surface of the porous base film away from the heat-resistant layer and / or the surface of the heat-resistant layer away from the porous base film by spin spraying and then dried to obtain a polymer layer. In this embodiment, when the coating amount of the polymer is, for example, 0.3 g / m 2 -0.7g / m 2 The coverage of the polymer layer is, for example, 25% to 60%. Further, when the coating amount of the polymer is, for example, 0.4 g / m 2 The coverage of the polymer layer is, for example, 30%-35%. If the coverage is too low, the overall adhesion of the diaphragm is too low, the effect of hot pressing and laminating the battery cell is poor, and interface wrinkles will be formed, thus affecting the cycle performance of the battery; if the coverage is too high, the overall air permeability of the diaphragm is too high, the overall impedance increases, and ultimately affects the cycle performance of the battery.

[0035] The present invention also provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the separator is located between the positive electrode sheet and the negative electrode sheet, and the electrolyte is filled between the positive electrode sheet, the negative electrode sheet and the separator, wherein the separator is selected from the above-mentioned separator. The present invention does not limit the type and shape of the lithium-ion battery. In one embodiment of the present invention, the lithium-ion battery is, for example, a primary battery or a secondary battery, wherein the secondary battery is, for example, a soft-pack battery, a square-shell battery or a cylindrical battery.

[0036] In one embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer coated on at least one surface of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. The thickness of the positive electrode current collector is, for example, 8μm-15μm. In this embodiment, the positive electrode current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm.

[0037] In one embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a positive electrode binder and a conductive agent. Among them, for example, at least one selected from lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA). The positive electrode binder is selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer (ETFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer (TFE-HFP-VDF) or tetrafluoroethylene-hexafluoropropylene copolymer (FEP). The conductive agent is selected from any one or more of conductive carbon black (Super P), acetylene black or Ketjen black. Among them, the mass ratio of the positive electrode active material, the conductive agent and the positive electrode binder in the positive electrode active layer is, for example, (90-97): (1-5): (2-5).

[0038] In one embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.6 Co 0.2 Mn 0.2O2, the positive electrode binder is selected from polyvinylidene fluoride, and the conductive agent is selected from acetylene black. After mixing the positive electrode active material, the conductive agent and the positive electrode binder in a mass ratio of 97:1:2, an organic solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. Among them, the organic solvent is selected from N-methylpyrrolidone (NMP), for example. The positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode sheet is obtained through processes such as cold pressing, trimming, cutting and striping. The present application does not limit the method for preparing the positive electrode sheet. In other embodiments, the positive electrode sheet can also be obtained by any other method of forming the positive electrode sheet.

[0039] In one embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector. The negative electrode current collector is, for example, selected from a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector, and the thickness of the negative electrode current collector is, for example, 8 μm-15 μm. In this embodiment, the negative electrode current collector is, for example, copper foil, and the thickness of the copper foil is, for example, 13 μm.

[0040] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a negative electrode binder, and a thickener. Among them, the negative electrode active material includes, for example, any one or more combinations of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, or lithium titanate. However, the present application is not limited to these materials, and other materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0041] In one embodiment of the present invention, the negative electrode binder is selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylic amide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) or carboxymethyl chitosan (CMCS). The thickener includes carboxymethyl cellulose sodium (CMC-Na) and the like, and the conductive agent is selected from any one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers and the like. The mass ratio of the negative electrode active material, the conductive agent, the negative electrode binder, and the thickener in the negative electrode active layer is, for example, (94-97):(1-2):(1-2):(1-2).

[0042] In one embodiment of the present invention, the negative electrode active material is selected from natural graphite, the conductive agent is selected from conductive carbon black, the thickener is selected from sodium carboxymethyl cellulose, and the negative electrode binder is selected from styrene-butadiene rubber. In one embodiment of the present invention, the negative electrode active material, the conductive agent, the thickener and the negative electrode binder are mixed, for example, in a mass ratio of 96:1:1:2, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained through cold pressing, trimming, cutting and stripping. In other embodiments, the negative electrode sheet can also be obtained by any other method of forming a negative electrode sheet.

[0043] In one embodiment of the present invention, the electrolyte includes, for example, an organic solvent and a lithium salt. The organic solvent is selected from any one or more of battery-grade ethylene carbonate (EC), propylene carbonate (PC), ethyl acetate (EA), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or diethyl carbonate (DEC). The lithium salt is selected from any one or more of lithium bis(fluorosulfonyl)imide (LiFSi), lithium difluorophosphate (LiPO2F2), lithium hexafluorophosphate (LiPF6) or lithium tetrafluoroborate (LiBF4). In one embodiment of the present invention, the lithium salt is selected from lithium hexafluorophosphate, for example, and the organic solvent is selected from a mixture of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and propylene carbonate. Ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and propylene carbonate are mixed, for example, in a volume ratio of 1:1:1:1, and in an argon atmosphere glove box with a water content of less than 10 ppm, fully dried LiPF6 is dissolved in the mixed organic solvent, and the mixture is mixed evenly to obtain an electrolyte, wherein the concentration of LiPF6 is, for example, 1 mol / L.

[0044] In one embodiment of the present invention, the positive electrode sheet, the separator and the negative electrode sheet are placed at intervals, and a bare cell is obtained by lamination or winding, and the bare cell is placed in a square shell, and then baked to remove water, and then the electrolyte is injected and sealed, and then the finished lithium-ion battery is obtained through the processes of standing, hot and cold pressing, formation, clamping and capacity division. Among them, the design capacity of the lithium-ion battery is, for example, 1000mAh.

[0045] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0046] Example 1

[0047] Preparation of the diaphragm: Take 90 parts by mass of water, add 0.0708 parts by mass of dispersant acrylic acid, 0.9292 parts by mass of the second binder acrylic polymer and 9 parts by mass of the first binder polymethyl methacrylate, stir evenly to form a 10wt% polymer slurry.

[0048] 2 parts by weight of the third binder polyacrylate and 60 parts by weight of water are stirred evenly, and 36 parts by weight of ceramic particles aluminum oxide are added and mixed evenly to form a 36.7wt% heat-resistant slurry. The ratio of the specific surface area / median particle size of the ceramic particles is in the range of 45, and the ratio of the median particle size of the third binder to the ceramic particles is 0.05.

[0049] The heat-resistant slurry is coated on a polyethylene film with a thickness of 10 μm and a porosity of 50% by micro-gravure printing, and a heat-resistant layer is formed after drying. The thickness of the heat-resistant layer is 2 μm. The polymer slurry is then sprayed on the surface of the heat-resistant layer and dried to obtain a polymer layer. The ratio of the mass of the dispersant per square meter of the polymer layer to the density of the first binder is 0.003, and the coating amount of the polymer layer is 0.5 g / m 2 , with a coverage rate of 40%.

[0050] Preparation of positive electrode: LiNi 0.6 Co 0.2 Mn 0.2 O2, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 97:1:2, and solvent N-methylpyrrolidone is added and stirred until it becomes uniform and transparent to obtain positive electrode slurry. The positive electrode slurry is evenly coated on aluminum foil, dried at room temperature, and then transferred to a vacuum drying oven for drying, and then cold pressed, trimmed, cut and stripped to obtain positive electrode sheets.

[0051] Preparation of negative electrode sheets: natural graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 96:1:1:2, deionized water is added, and the mixture is evenly mixed under the action of a vacuum mixer to obtain a negative electrode slurry, which is coated on a copper foil, and then dried at room temperature and transferred to an oven for drying. After cold pressing, trimming, cutting and slitting, a negative electrode sheet is obtained.

[0052] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and propylene carbonate are mixed, for example, in a volume ratio of 1:1:1:1, and in an argon atmosphere glove box with a water content of less than 10 ppm, fully dried LiPF6 is dissolved in a mixed organic solvent, and the mixture is mixed evenly to obtain an electrolyte, wherein the concentration of LiPF6 is, for example, 1 mol / L.

[0053] Preparation of battery: stack the above positive electrode sheet, separator and negative electrode sheet in sequence to obtain a bare cell, with the separator placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. Put the bare cell into the shell, bake it to remove water, inject electrolyte and seal it, and then go through the processes of standing, hot and cold pressing, formation, clamping and capacity division to obtain a finished lithium-ion battery with a capacity of 1000mAh.

[0054] Example 2

[0055] The content of dispersant and binder in the polymer slurry is controlled, and the ratio of the mass of dispersant in each square meter of polymer layer to the density of the first binder is 0.005. The coating amount of the polymer layer is 0.5g / m 2 , the coverage rate is 40%, and the remaining steps are the same as Example 1.

[0056] Example 3

[0057] The content of dispersant and binder in the polymer slurry is controlled, and the ratio of the mass of dispersant in each square meter of polymer layer to the density of the first binder is 0.002. The coating amount of the polymer layer is 0.5g / m 2 , the coverage rate is 35%, and the remaining steps are the same as in Example 1.

[0058] Example 4

[0059] The ratio of the specific surface area / median particle size of the ceramic particles ranges from 40. The coating amount of the polymer layer is 0.5 g / m 2 , the coverage rate is 40%, and the remaining steps are the same as Example 1.

[0060] Example 5

[0061] The ratio of the specific surface area / median particle size of the ceramic particles is in the range of 80. The coating amount of the polymer layer is 0.5 g / m 2 , the coverage rate is 40%, and the remaining steps are the same as Example 1.

[0062] Example 6

[0063] The ratio of the median particle size of the third binder to the ceramic particles is 0.07, and the coating amount of the polymer layer is 0.5 g / m 2 , the coverage rate is 40%, and the remaining steps are the same as Example 1.

[0064] Example 7

[0065] The ratio of the median particle size of the third binder to the ceramic particles is 0.1, and the coating amount of the polymer layer is 0.5 g / m 2 , the coverage rate is 40%, and the remaining steps are the same as Example 1.

[0066] Example 8

[0067] The ceramic particles were replaced with silicon dioxide, and the remaining steps were the same as in Example 1.

[0068] Example 9

[0069] Control the content of dispersant and binder in the polymer slurry, and the coating amount of the polymer layer is 0.3g / m 2The coverage rate is 25%, the ratio of the mass of the dispersant in each square meter of the polymer layer to the density of the first binder is 0.003, and the remaining steps are the same as in Example 1.

[0070] Example 10

[0071] Control the content of dispersant and binder in the polymer slurry, and the coating amount of the polymer layer is 0.4g / m 2 The coverage rate is 35%, the ratio of the mass of the dispersant in each square meter of the polymer layer to the density of the first binder is 0.003, and the remaining steps are the same as in Example 1.

[0072] Embodiment 11

[0073] Control the content of dispersant and binder in the polymer slurry, and the coating amount of the polymer layer is 0.6g / m 2 , the coverage rate is 50%, the ratio of the mass of the dispersant in each square meter of the polymer layer to the density of the first binder is 0.003, and the remaining steps are the same as in Example 1.

[0074] Example 12

[0075] Control the content of dispersant and binder in the polymer slurry, and the coating amount of the polymer layer is 0.7g / m 2 The coverage rate is 60%, the ratio of the mass of the dispersant in each square meter of the polymer layer to the density of the first binder is 0.003, and the remaining steps are the same as those in Example 1.

[0076] Comparative Example 13

[0077] The ratio of the specific surface area / median particle size of the ceramic particles is in the range of 30, and the remaining steps are the same as those in Example 1.

[0078] Comparative Example 14

[0079] The ratio of the specific surface area / median particle size of the ceramic particles is in the range of 90, and the remaining steps are the same as those in Example 1.

[0080] Comparative Example 15

[0081] The ratio of the median particle size of the third binder to the ceramic particles is 0.004, and the remaining steps are the same as those in Example 1.

[0082] Comparative Example 16

[0083] The ratio of the median particle size of the third binder to the ceramic particles is 0.12, and the remaining steps are the same as in Example 1.

[0084] Comparative Example 1

[0085] The content of dispersant and binder in the polymer slurry was controlled, the mass ratio of the dispersant to the density of the first binder was 0.001, and the coating amount of the polymer layer was 0.5 g / m 2 , the coverage rate is 40%, and the remaining steps are the same as Example 1.

[0086] Comparative Example 2

[0087] The content of dispersant and binder in the polymer slurry was controlled, the mass ratio of the dispersant to the density of the first binder was 0.01, and the coating amount of the polymer layer was 0.5 g / m 2 , the coverage rate is 40%, and the remaining steps are the same as Example 1.

[0088] Comparative Example 3

[0089] The content of dispersant and binder in the polymer slurry was controlled, the mass ratio of the dispersant to the density of the first binder was 0.003, and the coating amount of the polymer layer was 0.2 g / m 2 , the coverage rate is 15%, and the remaining steps are the same as in Example 1.

[0090] Comparative Example 4

[0091] Control the content of dispersant and binder in the polymer slurry, and the coating amount of the polymer layer is 0.8g / m 2 The coverage rate is 65%, the ratio of the mass of the dispersant in each square meter of the polymer layer to the density of the first binder is 0.003, and the remaining steps are the same as in Example 1.

[0092] In the present invention, the performance of the lithium ion batteries obtained in Examples 1-16 and Comparative Examples 1-4 was tested, and the test results are shown in Table 1.

[0093] In one embodiment of the present invention, the method for testing the coating amount of the polymer layer is:

[0094] The diaphragms prepared in Examples 1-16 and Comparative Examples 1-4 were taken as samples. First, the average thickness of the sprayed layer was confirmed: after stacking ten layers of the diaphragm, the overall thickness of the diaphragm was measured with a micrometer T1. After the diaphragm was ion-polished, a cross-sectional analysis was performed. The total thickness of the base film and the heat-resistant layer in the single-layer diaphragm was measured with a scanning electron microscope (SEM) as T2, and T1 / 10-T2 was the average thickness of the polymer layer. The coverage of the polymer layer was measured with a charge-coupled device detector (CCD) as S1. The coating amount of the sample = (T1 / 10-T2)*S1*ρ, where ρ is the density of the polymer layer;

[0095] Alternatively, the batteries prepared in Examples 1-16 and Comparative Examples 1-4 are disassembled to obtain a diaphragm, and the batteries obtained after cleaning and natural air drying are used as samples. First, the average thickness of the spray layer is confirmed: after stacking ten layers of diaphragms, the overall thickness of the diaphragm is measured with a micrometer T1, and the diaphragm is ion-polished and cross-sectionally analyzed. The sum of the thickness of the base film and the heat-resistant layer in the single-layer diaphragm is measured with a scanning electron microscope as T2, and T1 / 10-T2 is the average thickness of the polymer layer. The coverage of the polymer layer is measured by a charge-coupled device detector as S1, and the coating amount of the sample is = = (T1 / 10-T2)*S1*ρ, where ρ is the density of the polymer layer.

[0096] In one embodiment of the present invention, the coverage of the polymer layer is tested by:

[0097] Based on the preparation process of the polymer layer obtained in Examples 1-16 and Comparative Examples 1-4, the coverage set in the preparation of the polymer layer in Examples 1-16 and Comparative Examples 1-4 was obtained;

[0098] Alternatively, take the membranes prepared in Examples 1-16 and Comparative Examples 1-4 as samples, use a three-dimensional digital microscope, place the membrane on the platform, align the microscope with the test position, set the magnification to 20 times, set the automatic area measurement, click Next, take a picture, and the device will automatically generate a coverage value;

[0099] Alternatively, disassemble the batteries prepared in Examples 1-16 and Comparative Examples 1-4 to obtain a diaphragm, use a three-dimensional digital microscope, place the diaphragm on a platform, align the microscope with the test position, set the magnification to 20 times, set automatic area measurement, click Next, take a picture, and the device will automatically generate a coverage value.

[0100] In one embodiment of the present invention, the material density is tested by:

[0101] The first binder used in Examples 1-16 and Comparative Examples 1-4 was taken as a sample, and the material density data was obtained according to GB / T1033.1-2008;

[0102] In one embodiment of the present invention, the specific surface area / median particle size of ceramic particles is tested as follows:

[0103] The ceramic particles used in the preparation process were taken as samples, and the specific surface area of ​​the ceramic particles was obtained by referring to GB / T39713-2020, and the median particle size of the ceramic particles was obtained by GB / T41949-2022;

[0104] Alternatively, the diaphragms prepared in Examples 1-16 and Comparative Examples 1-4 are taken as samples. Method 1: After calcining at 600° C. for 120 hours, the ceramic particles are filtered to obtain ceramic particles, which can be repeatedly calcined, filtered and purified until the test requirements of GB / T39713-2020 and GB / T41949-2022 are met; Method 2: The sample is ultrasonically dissolved and shaken in NMP for 10 hours, and ceramic particles are obtained after washing and filtering. The ceramic particles can be repeatedly ultrasonically dissolved and shaken until the ceramic particles obtained are filtered until the test requirements of GB / T39713-2020 and GB / T41949-2022 are met;

[0105] Alternatively, the batteries prepared in Examples 1-16 and Comparative Examples 1-4 are disassembled to obtain a diaphragm, and then ceramic particles are obtained by method 1 or method 2, and tested to obtain the specific surface area and median particle size of the ceramic particles.

[0106] In one embodiment of the present invention, the coating thickness is obtained, for example, by a scanning electron microscope test, and the roughness of the heat-resistant layer is obtained, for example, by a surface roughness meter test.

[0107] In one embodiment of the present invention, the membrane impedance test is obtained by preparing the membranes obtained in Examples 1-16 and Comparative Examples 1-4 into Li-Li symmetric batteries and then performing electrochemical impedance spectroscopy (EIS) testing.

[0108] In one embodiment of the present invention, the polymer coating adhesion test is to take the diaphragm and the positive electrode plate in a hot press, hot press them at 95°C and a pressure of 3Mpa for 60s, cut the hot-pressed composite into 200mm*15mm splines, and take 3 splines for testing respectively: open the lower end of the spline, clamp the electrode plate in the lower clamp of the tensile testing machine, pull the diaphragm in the opposite direction and clamp it to the upper clamp, start the tensile testing machine, and the stretching rate is 50mm / min. After the sample is peeled off, the average adhesion of the 3 splines is read.

[0109] In one embodiment of the present invention, the interface wrinkle performance test is to disassemble the battery cell after it is fully charged, observe the wrinkles of the negative electrode plate, and compare it with the fully charged interface of the battery cell prepared in Example 1, count the number of wrinkles on the electrode plate to be tested, and calculate the reduction ratio of the number of wrinkles on the electrode plate to be tested compared with the number of wrinkles on the electrode plate of the battery cell prepared in Example 1.

[0110] In one embodiment of the present invention, the cycle test of the lithium-ion battery is to perform long-cycle charge and discharge on the lithium-ion battery prepared above at 25°C, measure its discharge capacity, and calculate the energy density. The working voltage range of the battery test is 2.5V-4.3V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded as the 1C discharge capacity. When the battery capacity reaches 80% (80% State of Health, 80% SOH) of the first cycle capacity, the test is terminated to obtain the number of cycles at room temperature.

[0111] Table 1 Performance test results of the separators and lithium-ion batteries in Examples 1-16 and Comparative Examples 1-4

[0112]

[0113] As shown in Table 1, by comparing Examples 1-3 and Comparative Examples 1-2, it can be seen that as the mass of the dispersant and the density ratio of the first binder increase, the diaphragm impedance first decreases and then increases, the battery cycle number first increases and then decreases, and the interface wrinkle performance improves. Therefore, controlling the mass of the dispersant and the density ratio of the first binder can reduce the diaphragm impedance, improve the battery cycle performance, and improve the interface wrinkle problem.

[0114] Please refer to Table 1. By comparing Examples 1, 4-5, 13-14, it can be seen that when the BET / Dv of the ceramic particles in the heat-resistant layer is 50 When the ratio is within the range of 40-80, the roughness of the heat-resistant layer, the impedance of the diaphragm, the adhesion of the polymer coating, the number of battery cycles, and the interface wrinkle performance are within the preferred range. When it is less than this range, the roughness of the heat-resistant layer becomes larger. When it is greater than this range, the roughness of the heat-resistant layer becomes larger, the impedance of the diaphragm increases, the adhesion of the polymer coating decreases, the number of battery cycles decreases, and the interface wrinkle performance deteriorates. Comparing Examples 1, 6-7, and 15-16, it can be seen that as the third binder Dv increases, the roughness of the heat-resistant layer increases, the impedance of the diaphragm increases, the adhesion of the polymer coating decreases, the number of battery cycles decreases, and the interface wrinkle performance deteriorates. 50 / Ceramic particles Dv 50 With the increase of the ratio, the roughness of the heat-resistant layer first decreases and increases, the impedance of the diaphragm first decreases and then increases, the adhesion of the polymer coating first increases and then decreases, the number of battery cycles first increases and then decreases, and the interface wrinkles first improve and then deteriorate. This shows that by controlling the ratio of the specific surface area / median particle size of the ceramic particles and the ratio of the median particle size of the third binder and the ceramic particles, the surface roughness of the heat-resistant layer is controlled, thereby improving the actual contact area between the heat-resistant layer and the polymer layer, increasing the effective bonding area, improving the adhesion between the heat-resistant layer and the polymer layer, and improving the overall adhesion of the diaphragm. The problem of cell interface wrinkles is improved, thereby improving the cycle performance of the battery.

[0115] Please refer to Table 1. By comparing Examples 1 and 8, it can be seen that when different types of ceramic particles are selected in heat resistance, the performance of the diaphragm and the battery are similar, indicating that different types of ceramic particles can improve the performance of the diaphragm.

[0116] As shown in Table 1, by comparing Examples 1, 9-12 and Comparative Examples 3-4, it can be seen that as the coating amount of the polymer layer increases, the coverage of the polymer layer increases, and the coating amount of the polymer layer is 0.3 g / m 2 -0.7g / m 2 , when the coverage of the polymer layer is in the range of 25%-60%, the impedance of the diaphragm is maintained in a lower range, the adhesion of the polymer coating increases with the increase of the coating amount, the number of battery cycles is maintained at a high level, and the interface wrinkle performance is improved. This is because the coverage is too low, the overall adhesion of the diaphragm is too low, the effect of hot pressing and compounding of the battery cell is poor, and interface wrinkles will be formed, thus affecting the cycle performance of the battery. If the coverage is too high, the overall air permeability of the diaphragm is too high, the overall impedance increases, and ultimately affects the battery cycle performance. Therefore, the present application can obtain a low coating amount and a high polymer layer coverage, the adhesion of the obtained diaphragm is improved, and the interface wrinkle problem is improved, the diaphragm impedance is reduced, and the long cycle performance of the battery is improved.

[0117] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.

[0118] In summary, the present invention proposes a diaphragm and its preparation method and application, which can improve the uniformity of the formed polymer layer and obtain a uniformly coated polymer layer. It is possible to improve the mechanical properties of the diaphragm while taking into account flexibility, improve the ion transmission performance of the diaphragm, reduce the contact area with the electrolyte, and improve the chemical stability of the diaphragm. The microscopic surface of the heat-resistant layer obtained is smooth and dense, and the actual contact area between the heat-resistant layer and the polymer layer is increased, thereby increasing the effective bonding area, improving the adhesion between the heat-resistant layer and the polymer layer, so that the overall adhesion of the diaphragm is improved, and the problem of cell interface wrinkles is improved, thereby improving the cycle performance of the battery. It is possible to improve the high temperature resistance of the diaphragm, improve the thermal shrinkage of the porous base film at high temperature, and ensure the smooth conduction of lithium ions. Through a low coating amount and a high polymer layer coverage, the adhesion of the obtained diaphragm is improved, the problem of interface wrinkles is improved, the diaphragm impedance is reduced, and the long cycle performance of the battery is improved.

[0119] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept, such as the technical solution formed by replacing the above features with the technical features with similar functions disclosed in this application (but not limited to). In addition to the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described in detail here.

Claims

1. A diaphragm, characterized in that: At least: Porous base membrane; A heat-resistant layer, disposed on at least one surface of the porous base membrane; as well as The polymer layer is disposed on the surface of the porous base film away from the heat-resistant layer and / or on the surface of the heat-resistant layer away from the porous base film, the polymer layer comprises a first binder, a second binder and a dispersant, and the coating amount of the polymer layer is 0.3 g / m 2 -0.7g / m 2 , the coverage of the polymer layer is 25%-60%.

2. The diaphragm according to claim 1, characterized in that The ratio of the mass of the dispersant in the polymer layer per square meter to the material density of the first binder is 0.002-0.005:1, and the material density of the first binder is 0.6 g / cm 3 -1.2g / cm 3 .

3. The diaphragm according to claim 1, characterized in that The first binder includes at least one of polymethyl methacrylate or acrylate; the second binder includes at least one of polyacrylate polymers, polyacrylonitrile or acrylic polymers, and the molecular weight of the second binder is greater than 600,000; the dispersant includes at least one of water-based styrene maleic anhydride, acrylic acid and its salts.

4. The diaphragm according to claim 1, characterized in that In the polymer layer, the mass ratio of the first binder to the dispersant is 75-400:1, and the mass ratio of the first binder to the second binder is 8-15:

1.

5. The diaphragm according to claim 1, characterized in that The median particle size of the first binder is 5 μm-10 μm, and the median particle size of the second binder is less than 1 μm.

6. The diaphragm according to claim 1, characterized in that The thickness of the heat-resistant layer is 0.5 μm-2 μm, and the bulk density of the heat-resistant layer is 1.2 g / cm 3 ~2.0g / cm 3 .

7. The diaphragm according to claim 1, characterized in that The heat-resistant layer includes ceramic particles, which include at least one of aluminum oxide, hydrated aluminum oxide, aluminum hydroxide, silicon dioxide, titanium dioxide, barium sulfate, barium titanate, magnesium hydroxide or magnesium oxide, and the structure of the ceramic particles is flaky, and the specific surface area / median particle size of the ceramic particles is in the range of 40-80.

8. The diaphragm according to claim 7, characterized in that The heat-resistant layer includes a third binder, and the ratio of the median particle size of the third binder to the median particle size of the ceramic particles is 0.01-0.1:

1.

9. A method for preparing the diaphragm according to any one of claims 1 to 8, characterized in that: include: Dispersing the first binder, the second binder and the dispersant in the first solvent according to a mass ratio to obtain a polymer slurry; After mixing the third binder and the second solvent, adding ceramic particles and mixing evenly to obtain a heat-resistant slurry; Applying the heat-resistant slurry on at least one surface of the porous base film and drying; as well as The polymer slurry is coated on a surface of the porous base membrane away from the heat-resistant layer and / or a surface of the heat-resistant layer away from the porous base membrane and dried.

10. A lithium ion battery, characterized in that: A diaphragm comprising any one of claims 1 to 8.